Alterations in resting‐state whole‐brain functional connectivity pattern similarity in bipolar disorder patients - Ping, Liangliang; Zhou, Cong; Sun, Shan; Wang, Wenqiang; Zheng, Qi; You, Zhiyi (Brain and behavior, 2022)
Background Previous neuroimaging studies have extensively demonstrated many signs of functionally spontaneous local neural activity abnormalities in bipolar disorder (BD) patients using resting‐state functional magnetic resonance imaging (rs‐fMRI). However, how to identify the changes of voxel‐wise whole‐brain functional connectivity pattern and its corresponding functional connectivity changes remain largely unclear in BD patients. The current study aimed to investigate the voxel‐wise changes of functional connectivity patterns in BD patients using publicly available data from the UCLA CNP LA5c Study. Methods A total of 45 BD patients and 115 healthy control subjects were finally included and whole‐brain functional connectivity homogeneity (FcHo) was calculated from their rs‐fMRI. Moreover, the alterations of corresponding functional connectivity were subsequently identified using seed‐based resting‐state functional connectivity analysis. Results Individuals with BD exhibited significantly lower FcHo values in the left middle temporal gyrus (MTG) when compared with controls. Functional connectivity findings further indicated decreased functional connectivities between left MTG and cluster 1 (left superior temporal gyrus, extend to middle temporal gyrus, rolandic operculum), cluster 2 (right postcentral, extend to right precentral) in BD patients. The mean FcHo values of left MTG were positively correlated with insomnia, middle scores and appetite increase scores. The mean functional connectivities of left MTG to cluster 1 were negatively correlated with grandiose delusions scores. While the functional connections between left MTG with cluster 2 were negatively correlated with delusions of reference and positively correlated with insomnia, middle scores in BD patients. Conclusions Our findings suggested that abnormal FcHo and functional connections in those areas of the brain involving DMN and SMN networks might play a crucial role in the neuropathology of BD. A total of 45 BD patients and 115 healthy control subjects were finally included and whole‐brain functional connectivity homogeneity (FcHo) was calculated from their rs‐fMRI. Seed‐based resting‐state functional connectivity analysis was then used to reveal the alteration of corresponding functional connectivity. Our findings indicated that whole‐brain FcHo and connectivity abnormalities of left middle temporal gyrus might play a crucial role in the neuropathology of BD.